Implementation of Communication Strategies by Traditional Market Traders Based on Islamic Broadcasting Values to Enhance Interaction with Buyers - Silvani Tiara Afrianda; Abdul Rasyid (STAI Publisistik Thawalib Jakarta, 2025)
Effective communication by traditional market traders strengthens social relationships, maintains buyer loyalty, reflects Islamic values, and serves as an adaptive strategy to face challenges from the modern and digital market. This study aims to analyze the communication strategies of traditional market traders based on Islamic broadcasting values and their influence on socio-economic interaction and buyer loyalty within a socio-cultural context. This research employs a qualitative case study approach with data collection techniques including participatory observation, in-depth interviews, and documentation, analyzed using thematic analysis. The findings indicate that traditional market traders' verbal and nonverbal communication strategies reflect Islamic broadcasting values, strengthen socio-economic relationships, build trust, and enhance buyer loyalty through friendly, ethical, and empathetic approaches. The socio-cultural context plays a crucial role in the communication strategies of traditional market traders, encouraging harmonious cross-cultural adaptation and reinforcing interactions based on Islamic values such as empathy, tolerance, and muamalah ethics (Islamic commercial ethics). Communication strategies grounded in Islamic values, such as friendliness, empathy, and ethics, prove effective in increasing buyer loyalty through emotional bonding, trust, and warm, humane shopping experiences in traditional markets. In conclusion, communication strategies based on Islamic values enhance socio-economic interactions, build loyalty, and adapt culture within multiethnic traditional markets.